1997
DOI: 10.1016/s0029-7844(97)00139-7
|View full text |Cite
|
Sign up to set email alerts
|

Serum triple-marker screening in in vitro fertilization and naturally conceived pregnancies

Abstract: The increased hCG levels as well as the slightly lower AFP and unconjugated E3 levels may contribute to the higher Down syndrome screen-positive rate in this IVF singleton population. These results may be due to the number of embryos transferred, the maternal hormonal environment of the IVF process, or other factors. Pregnancies conceived by IVF may be twice as likely to have a positive maternal serum screening test. As additional data are collected, corrected standards should be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 8 publications
5
38
0
Order By: Relevance
“…Previous studies in the second trimester reported that in pregnancies conceived by in vitro fertilization, compared to spontaneous conceptions, the levels of serum AFP were either higher, lower or not significantly different [28][29][30][31][32][33][34][35][36][37][38][39] . Only one previous study examined the effect of ovulation induction in second-trimester serum AFP and although there was no overall significant difference from spontaneous conceptions, there was an increase if treatment was with clomiphene and a decrease when pergonal was used [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in the second trimester reported that in pregnancies conceived by in vitro fertilization, compared to spontaneous conceptions, the levels of serum AFP were either higher, lower or not significantly different [28][29][30][31][32][33][34][35][36][37][38][39] . Only one previous study examined the effect of ovulation induction in second-trimester serum AFP and although there was no overall significant difference from spontaneous conceptions, there was an increase if treatment was with clomiphene and a decrease when pergonal was used [28] .…”
Section: Discussionmentioning
confidence: 99%
“…An improved method with a detection rate of about 60% of affected pregnancies was the combination of maternal age with second trimester maternal biochemistry [Orlandi et al, 1997]. However, studies on maternal serum screening for aneuploidy in IVF pregnancies reported reduced AFP and elevated HCG concentrations, leading to a higher than expected positive screening rate [Frishman et al, 1997;Ribbert et al, 1996]. Recently, this observation was confirmed for ICSI pregnancies too [Lam et al, 1999].…”
Section: Possible Applications Of Noninvasive Techniques Of Prenatal mentioning
confidence: 99%
“…In ART pregnancies maternal serum marker levels change during the first trimester affecting the risk assessment for DS [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26]. Counseling for prenatal screening of women carrying an ART pregnancy is complicated due to contradictory reports in FTS performance in ART pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Counseling for prenatal screening of women carrying an ART pregnancy is complicated due to contradictory reports in FTS performance in ART pregnancies. Several studies reported higher false-positive rate (FPR) compared to spontaneously conceived pregnancies [5,6,7,8,9,10,11], some studies found higher FPR even after correction for maternal age [12,13,14,15] and others reported similar FPR [16,17,18,19,20]. Whether the prevalence of fetal chromosomal abnormalities in ART pregnancies is different from naturally conceived pregnancies is however unclear.…”
Section: Introductionmentioning
confidence: 99%